2011
DOI: 10.1038/eye.2011.110
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fine vascular network pattern associated with recurrence of polypoidal choroidal vasculopathy

Abstract: Objective To characterize an irregular capillary-like structure in the vascular network of eyes with polypoidal choroidal vasculopathy (PCV), and to determine whether its presence after photodynamic therapy (PDT) can be used to predict the clinical course of PCV. Methods We reviewed the clinical records of 29 eyes of 29 patients with PCV, who underwent PDT and confocal retinal angiographic examinations every 3 months. The images obtained before the PDT were compared with those after the PDT. The correlations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…A previous study investigating ICG of polypoidal choroidal vasculopahy (PCV) patients reported that fine and dense capillary vessels (compatible with our defined DN) are associated with recurrence after PDT (Oishi et al 2011). A previous study investigating ICG of polypoidal choroidal vasculopahy (PCV) patients reported that fine and dense capillary vessels (compatible with our defined DN) are associated with recurrence after PDT (Oishi et al 2011).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A previous study investigating ICG of polypoidal choroidal vasculopahy (PCV) patients reported that fine and dense capillary vessels (compatible with our defined DN) are associated with recurrence after PDT (Oishi et al 2011). A previous study investigating ICG of polypoidal choroidal vasculopahy (PCV) patients reported that fine and dense capillary vessels (compatible with our defined DN) are associated with recurrence after PDT (Oishi et al 2011).…”
Section: Discussionsupporting
confidence: 60%
“…Further studies implementing vascular growth behaviour may deliver more detailed insight into CNV progression and treatment response. A previous study investigating ICG of polypoidal choroidal vasculopahy (PCV) patients reported that fine and dense capillary vessels (compatible with our defined DN) are associated with recurrence after PDT (Oishi et al 2011). Spaide et al (2015;Spaide 2015) presented a descriptive study of treated CNV eyes secondary to AMD based on OCTA receiving periodic anti-VEGF injections.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, BVN was noted outstandingly in the early phase of ICGA; meanwhile, LGH was determined in the late phase (figure 2). Recently, the angiographic feature of a fine irregular vascular network pattern was described, which was clinically similar to LGH; this pattern was correlated with recurrence 9 12. The authors thus suspected that LGH was an angiographic feature of leakage from the vascular network.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it could be below the baseline value 5 years after the treatment [123,124,125]. Persistent BVN may be the origin of new polypoidal lesions [126]. In a recent prospective cohort study, 56 out of 139 eyes (40%) in the tAMD cases and 52 out of 107 eyes (49%) in the PCV cases were recurrent during the 60 months of follow-up after the initial PDT [123].…”
Section: Response To Treatmentmentioning
confidence: 99%